Desmin 370, a Low Molecular Weight Dermatan Sulfate, Reduces the Weight of Preformed Thrombi in Rats Made Afibrinogenemic by Ancrod - Barbanti, Miriam; Calanni, Fiorella; Marchi, Egidio; Semeraro, Nicola; Colucci, Mario (Thrombosis and Haemostasis, 1995)
Desmin 370 (D370), a low molecular weight dermatan sulfate, has been shown to induce a marked reduction of the weight of preformed venous thrombi in rats and rabbits by mechanisms that appeared largely independent of inhibition of thrombus accretion. In order to provide further support for such a mechanism, we exploited the defibrinating capacity of ancrod to obtain a thrombosis model characterized by the lack of thrombus growth and thus sensitive only to agents promoting thrombus lysis. Thrombus formation in anesthetized rats was induced by vena cava ligature. Injection of ancrod (5 U/kg) 5 h after induction of venous stasis caused a more than 95% reduction in plasma fibrinogen and prevented thrombus accretion as indicated by the lack of thrombus weight increase during the 3h experimental period (12.2 ° 0.6 vs 14.5 ° 1 as compared to 12.6 ° 0.6 vs 19.6 ° 0.8, p <0.01, in control rats) and by the almost complete (>90%) inhibition of125I- fibrin(ogen) binding to thrombi. Moreover, when ancrod was given 1 h before vena cava ligature, no thrombi were formed within 2 h whereas at the same time interval visible thrombi were present in all control rats. Administration of D370 (10 mg/kg) to thrombus bearing rats, 1 h after induction of afibrinogenemia, resulted in a significant reduction in thrombus weight (43% after 2h, p <0.01) which was only slightly lower than that recorded in normofibrinogenemic rats (54%). Enhancement of plasma fibrinolytic activity by ancrod had no influence on thrombus lysis and was not at all affected by administration of D370. These data provide additional and more direct evidence that D370 may promote thrombus lysis independently of inhibition of thrombus accretion.